Do self-awareness and behavioural biases impact ethics compliance? A student's perspective - Sibarani, Blasius Erik; Wiharsianti, Ervilia Agustine (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
This study aims to investigate the impact of self-awareness and behavioural biases on students' ethics compliance. In the context of rapid development, ethics is becoming an increasingly important issue both in and outside the academic sphere. Ethics is a moral value that guides individuals or groups in acting and behaving. A person's moral character is formed early through the influence of the family, culture, and religious environment. Good ethical knowledge can affect a person's moral understanding and awareness. The sample analyzed in this study amounted to 100 respondents consisting of high school students and college students. The data is analyzed with the help of SmartPLS. SmartPLS allows researchers to test relationships between variables in a model using PLS methods. Hypothesis testing is carried out with a path coefficient that looks at the p-value at a significance level of 5%. The results of this study show that self-awareness has a positive impact on students' ethics compliance, and behavioural biases have a negative impact on students' ethics compliance